UPANISAD PERSPEKTIF PENDIDIKAN MODERN - Ida bagus Putu eka Suadnyana; Krisna Sukma Yogiswari (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2019)
Book of the Upanishads is a book that can guide students to improve Sradha and Bhakti presented to Ida Sang Hyang Wasa Widhi. Upanishad is taken from the word